Implementasi Keperawatan Silent Treatment Pada Pasien Skizofrenia Dengan Resiko Perilaku Kekerasan - Pastari, Marta; Martini, Sri; Sumastri, Heni; Athiutama, Ari; Febriani, Indra; Aguscik, Aguscik; Prasetyo, Bagas (JKM : Jurnal Keperawatan Merdeka, 2025)
Background: Risk Violent behavior is a type of risky behavior directed towards oneself, others, or the environment. Aggressive behavior towards oneself can lead to self-harm actions up to suicide or neglecting oneself in the form of self-neglect. Violence against others is an act of aggression with the intent to cause harm or make others suffer. Objective: To describe the implementation of behavioral therapy in patients with schizophrenia who have issues with violent behavior risk. Method: Method In this study, the author uses a descriptive method where the researcher will describe the implementation of behavioral therapy at Ernaldi Bahar Hospital in South Sumatra Province. Results: The implementation of behavioral therapy on schizophrenia patients with a risk of violent behavior can be carried out well according to the established plan. The researchers evaluated the four patients and found that the implementation of behavioral therapy could help the patients control feelings of annoyance and anger, making them calmer and less prone to quick emotional outbursts, thereby reducing the symptoms of violent behavior risk experienced by the patients. Conclusion: The researcher hopes that the patients can maintain and implement what has been taught to them on how to control the risk of violent behavior through behavioral therapy. The researcher also hopes for the involvement of the patient's family in helping the patient control the risk of violent behavior by reminding or motivating the patient not to stop taking medication.